Endoscopic surgery of the orbit : anatomy, pathology, and management - Bleier, Benjamin S.; Freitag, Suzanne K.; Sacks, Raymond (Otolaryngologist) (Thieme, 2019)
"The field of endoscopic orbital surgery is one of the most rapidly advancing areas in modern day rhinology and oculoplastic practice and despite extensive research efforts, there is currently no text dedicated to the subject. Over the past decade and particularly over the past 2-3 years, there has been tremendous advancement in both the knowledge and surgical techniques involved in orbital surgery. This text provides a fully comprehensive review of all the Anatomy, Pathology and Physiology pertaining to the Orbit, Paranasal sinuses and surrounding structures in the region. The book then progresses to detail the management of the spectrum of pathologies encountered in the region and to debate all the pros and cons of differing treatment approaches with current evidence based medicine. It contains both radiologic and anesthetic considerations and details post-operative management of these patients"--Provided by publisher